PERAN PENDIDIKAN AGAMA KRISTEN DALAM PROGRAM PENGUATAN PENDIDIKAN KARAKTER (PPK) UNTUK MENCEGAH PERUNDUNGAN DI KELAS X SMAN 4 PALANGKA RAYA - Sinta Puji Astuti; Rudie; Yoan Colina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the role of Christian Religious Education in the Character Education Strengthening Program to prevent bullying in class X at SMAN 4 Palangka Raya. Bullying remains a serious issue in Indonesian secondary schools, including social exclusion and verbal harassment. This study aims to describe the implementation of Christian Religious Education within the Character Education Strengthening Program, identify supporting and inhibiting factors, and analyze its role in preventing bullying. This research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The informants consisted of a Christian Religious Education teacher, the Character Education Strengthening Program coordinator, and six tenth-grade students. Data were analyzed using the Miles and Huberman model. The results showed that the implementation of Christian Religious Education within the Character Education Strengthening Program has been conducted effectively through worship activities, group prayers, Bible reading, reflection on God's Word, social activities, and teacher role modeling. Supporting factors included support from the school, parents, and a conducive environment, while inhibiting factors included limited time, the influence of social media, and low student awareness. Christian Religious Education plays an important role in fostering love, empathy, tolerance, and mutual respect, making it effective in preventing bullying behavior and contributing to creating a safe and character-based school environment.